The Bears in the bed and the great big storm - Bright, Paul, 1949- (Good Books, 2008)
One by one, three young bears crawl into Bear and Mrs. Bear's bed during a thunderstorm, certain they hear monsters outside, and although Bear tells each that monsters are not real, he later changes his mind.